Sensitive Analysis for the Efficiency of a Parabolic Trough Solar Collector Based on Orthogonal Experiment - Xiaoyan Liu; Jing Huang; Qianjun Mao (International Journal of Photoenergy)
A multitude of the researches focus on the factors of the thermal efficiency of a parabolic trough solar collector, that is, the optical-thermal efficiency. However, it is limited to a single or double factors for available system. The aim of this paper is to investigate the multifactors effect on the system’s efficiency in cold climate region. Taking climatic performance into account, an average outlet temperature of LS-2 collector has been simulated successfully by coupling SolTrace software with CFD software. Effects of different factors on instantaneous efficiency have been determined by orthogonal experiment and single factor experiment. After that, the influence degree of different factors on the collector instantaneous efficiency is obtained clearly. The results show that the order of effect extent for average maximal deviation of each factor is inlet temperature, solar radiation intensity, diameter, flow rate, condensation area, pipe length, and ambient temperature. The encouraging results will provide a reference for the exploitation and utilization of parabolic trough solar collector in cold climate region.